PENDIDIKAN ISLAM PADA PERIODISASI MAKKAH - Drs. H Firdaus (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2017)
The early history of Islamic education developed in line with the emergence of Islam itself was set forth the Prophet Muhhamad saw, who was the first teacher and educator of Islam. In connection with this, education in the time of the Prophet is divided into two periods namely the period of Makkah and Medina. The period of education of the Prophet in Makkah lasted for approximately 13 years at this time is the effort of human liberation from the shackles of aqeedah which is adhered to by kurais group, with the aim to foster a Muslim person to become a cadre of big soul and can be prepared to become an Islamic Society, Muballiq and good educator, that is by inculcating the values of faith, based on Al-Qur'an and Hadith. In the process of education, the Prophet used the method based on individual approach, then extended to the family approach which in turn extended to the Society